PENGARUH RASA TAKUT KETINGGALAN (FOMO), KONTROL DIRI, DAN PENGARUH TEMAN SEBAYA TERHADAP PERILAKU PEMBELIAN IMPULSIF DI KALANGAN MAHASISWA - Pramestha, Nisa Vialmaida; Sakti, Norida Canda (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2026)
Impulsive behavior among students is an issue that often leads to negative consequences, both in terms of financial management and decisions related to their studies. The purpose of this study is to analyse the extent to which FOMO, self-control, and the influence of peer groups play a role in impulsive behavior among students enrolled in the 2022 Economics Education Study Program. This study applies an explanatory associative design combined with a quantitative method. The entire population consisting of 98 participants was sampled using saturated sampling technique. Analysis of the data was performed using multivariate linear regression using IMB SPSS Statistics 22 software. The analysis findings indicate that FOMO and peer influence have a favourable and substantial impact on impulsive buying behavior. Self-control variables were found to have no discernible impact. The implications of this research underscore the importance of a more holistic financial literacy education strategy, one that emphasizes not only strengthening self-control but also the ability to cope with digital and social pressures.